What's new in XSLT 2.0 a new face for XML transformations. - Kenton, Jeff
The XSLT version 1.0 language definition has been an official recommendation of the W3C since 1999. Its use has expanded dramatically in the past 18 months, for processing XML and XML/SOAP security policies and for generating HTML Web pages.